Answer:
2y + 2z
Step-by-step explanation:
-x + 2z + x + 2y
= (-1 + 1)x + 2y + 2z
= 2y + 2z
Hope this helped!
A^2+b^2=c^2 so 4(4) +3(3) is 16+9= 25 and the square root of that is 5.
Answer:
lol it so easy man 3(y+4) is the answer
Answer:
The equation has no solutions
Step-by-step explanation:
If we re arrange the equation a little more we will obtain the following
|x|=-11
Which is a contradiction since, the |x| is always a positive number
Attached is the representation of this function y= |x|
It means, that it doesnt matter what value 'x' has, the answer is the same number but, positive